ATTRACTION OF CULINARY TOURISM DESTINATIONS TO PROMOTE SUSTAINABILITY DEVELOPMENT DURING THE PANDEMIC - Agustina Multi Purnomo (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Culinary tourism had the most extensive product portfolio and was one of the tourism sectors most affected by the pandemic in Indonesia. The website was a specific communication tool for promoting tourism. The study objective was to examine how the government's promotion of culinary tourism in official website content strengthens the sustainability of culinary tourism development during the pandemic. This study used qualitative content analysis on the official tourism promotion website of the Indonesian government, namely https://www.indonesia.travel. Two hundred twenty-four articles on the